Unregistered Marriages in Tanah Datar Regency: Causes, Impacts, and Solutions - Eli, Elimartati; Arifki, Arifki Budia Warman; Firdaus, Firdaus; Ariful, Ariful Akmi; Mulyadi, Mulyadi Putra (ADHKI: JOURNAL OF ISLAMIC FAMILY LAW, 2024)
Objective: This article seeks to elucidate the causes, impacts, and potential solutions to the issue of unregistered marriages in Tanah Datar Regency. Research on unregistered marriages has been extensively conducted in Indonesia, revealing an increasing array of reasons for their occurrence. Prior studies identified three to five primary causes of unregistered marriages. This article presents additional findings regarding these causes, highlights specific violations of customary law provisions, and discusses the solutions implemented by relevant agencies to address the problem of unregistered marriages. The research adopts a qualitative approach and utilises both primary and secondary data sources. Methods: Data collection techniques involved interviewing 35 community leaders, analysing documentation from pertinent agencies, and conducting Focus Group Discussions (FGDs) with 50 participants from related sectors. Results: The research identified 11 distinct causes of unregistered marriages, including specific violations of customary rules, tribal marriages, non-conforming marriages, and marriages involving 'melompat pagar'. The negative consequences stemming from unregistered marriages are significant; most unregistered marriages within the community lack legal validity. This situation leads to complications for children born as a result of these unions, as issues surrounding custody and divorce in unregistered marriages are often resolved solely through customary law, lacking formal legal recognition. Conclusion: Given the substantial prevalence of unregistered marriages in Tanah Datar Regency, various solutions have been implemented by relevant agencies to address the challenges faced by individuals involved in such marriages. Initiatives by the DUKCAPIL include the issuance of a letter of absolute responsibility (SPTJM) for the purpose of creating family cards, birth certificates, and ID cards. The Batusangkar Religious Court addresses cases of isbat marriage and cumulative requests for divorce and polygamy. Additionally, the KUA offers solutions such as remarriage and the formalisation of new marriages.